TRANSFORMATION OF ETHYL-P-METHOXYCINNAMATE TO P –METHOXYCINNAMIC ACID FROM KENCUR (Kaempheria galanga L.) AND THEIR ANTIBACTERIAL ACTIVITY - Muhamad Salman Fareza; Rehana Rehana; Nuryanti Nuryanti; Didin Mujahidin (UNIVERSITAS SEBELAS MARET (UNS), 2017)
This study aimed to evaluate the antibacterial properties of ethyl-p-methoxycinnamate and p-methoxycinnamate acid from Kaempheria galanga L. Ethyl-p-methoxycinnamate was isolated from the n-hexane rhizome extract of Kaempheria galanga L. Separation and purification of this compound was carried out with vacuum liquid chromatography and column chromatography. Hydrolysis of ethyl-p-methoxycinnamic under alkaline conditions obtained p-methoxycinnamic acid with a good yield of 85 %. The structure of the compounds were charactrized with IR, NMR spectrophotometer (1H-NMR and 13C-NMR) and mass spectrophotometer. The antibacterial properties of the compounds were evaluated using microdilution methods against B. cereus ATCC 11778, L. monocytogenes ATCC 7644, E. coli ATCC 25922, S. enterica sv Typhimurium ATCC 14028, and E. aerogenes ATCC 13048. The compounds showed weak antibacterial properties. Only ethyl p-methoxycinnamate showed the strongest antibacterial activity, especially against B. cereus ATCC 11778 bacteria with MIC values of 62.5 mg /mL. The change of the functional groups provided no significant impact on the antibacterial activity.